Pengembangan Dashboard Monitoring Data Pasien Berbasis Business Intelligence untuk Mendukung Pengambilan Keputusan Klinis - Ahmad Rizky Pratama; Dinda Maharani Putri; Farhan Aditya Saputra (Journal of Medical and Health Science, 2026)
Abstract Digital transformation in the healthcare sector has increased the volume of patient data generated by various hospital information systems, such as electronic medical records, laboratory, radiology, pharmacy, and administrative applications. However, this vast amount of data does not always facilitate rapid and accurate decision-making, as information is often scattered and fragmented across different platforms. Business Intelligence (BI) offers an effective approach to integrating, analyzing, and visualizing health data through interactive dashboards for healthcare professionals and hospital management. This study aims to develop a BI-based patient monitoring dashboard model that provides real-time information to support clinical and operational decisions. A narrative literature review methodology was employed, examining studies related to health dashboards and BI implementation in healthcare organizations. The review findings indicate that BI-based dashboards can enhance patient monitoring, accelerate information access, improve operational efficiency, and support data-driven decision-making. The proposed model comprises layers for data integration, data warehousing, business analytics, and interactive visualization, all connected via real-time data flows. This research yields a conceptual framework to guide BI implementation, thereby sustainably improving service quality, organizational performance, and decision-making effectiveness within modern healthcare institutions.